Risking Border Instability: the Russian-Estonian Case - P. Jolicoeur; F. Labarre (Международная аналитика, 2020)
In international relations, the last three decades have been marked by national and institutional fragmentation. The fate of Yugoslavia and the Soviet Union, and the regrettable way that events played out (especially in the former case), could befall other federative entities as well. Canada and Belgium come to mind, as do countries like Spain, all of which effectively function as federations. However, while federations usually have dispute settlement and mechanisms for secession embedded in their constitutions, sub-constitutive territories are often excluded from such considerations. What territories such as Kosovo, Sandjak, Abkhazia, South Ossetia, etc. have in common is that they share a desire for independence from their parent country. However, achiveing independence would present risks to the territorial integrity of other countries (what can be termed the domino principle), as well as risks to the endurance of flexible international law. The cases we have alluded to above culminated in the Crimean crisis. The problems between Estonia and the Russian Federation stem from the choice of precedent and founding text on which to base the former’s renewed independence. While Estonia was founded on the basis of the 1920 Tartu Peace Treaty that put an end to the country’s War of Independence, its experience as a Soviet Republic added another legislative filter in the form of the 1977 Constitution of the Soviet Union. However, the principle of uti possidetis had evolved to apply to more than cases of colonialism. Thus, when Estonia seceded from the USSR with the borders it had been since 1945, it was doing so under the principle of uti possidetis. The current dispute stems from the fact that the Estonian political elite seek to have the 1920 Tartu Peace Treaty recognized as the foundational document for the country’s renewed independence. Under the Treaty, Estonian sovereignty applied over a much larger territory. By insisting that any new border arrangement with Russia be based on that Treaty, Estonia is invalidating the principle of uti possidetis and the validity of the Constitution of the Soviet Union as a vehicle for independence. It implies a latent Article 5 situation between NATO and Russia, and threatens the legitimacy of other post-Soviet secessions.